Wave propagation in functionally graded piezoelectric rods with rectangular cross-section - Yu, J.G.; Zhang, B.; Lefebvre, J.E.; Zhang, CH. (Archives of Mechanics, 2015)
For the purpose of design and optimization of functionally graded piezoelectric material (FGPM) transducers, wave propagation in FGPM structures has received much attention in the past twenty years. But research focused essentially on semi-infinite structures and one-dimensional structures, i.e., structures with a finite dimension in only one direction, such as horizontally infinite flat plates and axially infinite hollow cylinders. This paper proposes a double orthogonal polynomial series approach to solve the wave propagation problem in a two-dimensional (2D) FGPM structure, namely, an FGPM rod with a rectangular cross-section. The dispersion curves and electric potential distributions are illustrated.